(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
In this interdisciplinary article, we employ scholarship from educational studies, cultural studies, geography, and sociology. We use graffiti texts we have encountered ourselves in places where we have lived or visited as examples of how graffiti becomes pedagogical. Theoretically, the concepts of public pedagogy, new mobilities, and affect theory — notably Sara Ahmed’s ideas — complement Doreen Massey’s ideas about place, space, and identity, and are cornerstones of our framework. As we consider them, pedagogy and learning are multidimensional processes, which involve intellect or cognition, affect or emotion, sensation, and perception. Place, space, and identity are taken up as sociomaterial phenomena, whose meanings develop as people, texts, physical structures, and various cultural artifacts come into contact with one another and with ideologies about what is (ab)normal and (un)desirable that circulate throughout and across societies. In presenting and discussing examples of graffiti texts we have encountered where we live or visit, we identify three pedagogical purposes that graffiti artists might employ: contemplation, reflection, and action. We close by considering implications for teaching and learning across disciplines, age groups, and context.